Archaeology on Screen: Representing Archaeology on Film in Serbia - Aleksandar Bandović (University of Belgrade, 2016)
Reading the popular culture may contribute to the reflexive view on a discipline such as archaeology. Film, as a part of popular culture, frequently unveils the hidden messages, which may be an echo of a discipline or its distorted image in the mirror. Film and archaeology share not only the common origins in the modernity, but also the imaginary spaces where the past and the present meet and intertwine. The subjects treated in films, the contexts in which archaeology appears, speak of the place the discipline holds in the society, reminding us at the same time of all the elements encompassed by the archaeological discourse. On the other hand, if we compare the portraits of the imaginary archaeologists (such as Professor Mihajlo Pavlović, Vera Zarić), with the witnesses of archaeology in Serbia over the 20th century (Nikola Vulić, Dragoslav Srejović, Milutin Garašanin), we shall approach the meeting point between academic and general public, science and the audience, theory and practice. Extraordinary individuals, unemployed dreamers living at the borders of the worlds, charming connoisseurs of the underworlds – these are but some of the qualities ascribed to the discipline by the films. However, these stereotypes do not generate out of the void, they are the consequence of the self-representation. This mystification of the discipline leads us back to the debate on the responsibility and ethics of the social scientists inside the society they live in. Of course, the suggested reading is one of the many possibilities, one of the archaeological interpretations.